The Protective Effect of Mycosporine-Like Amino Acids (MAAs) from Porphyra yezoensis in a Mouse Model of UV Irradiation-Induced Photoaging - Rui Ying; Zhaohui Zhang; Huiying Zhu; Bafang Li; Hu Hou (Marine Drugs, 2019)
The objective of this research was to extract and prepare mycosporine-like amino acids (MAAs) and investigate the mechanism by which they act against UV-induced skin photoaging in Institute of Cancer Research (ICR ) mice. MAAs such as porphyra-334 and shinorine were extracted from Porphyra yezoensis, separated, and purified using column chromatography with SA-2 cation exchange resin. The effects of MAAs on the activity of endogenous antioxidant enzymes, namely total superoxide dismutase (T-SOD), glutathione peroxidase (GSH-Px), catalase (CAT), and malondialdehyde (MDA) were analyzed in mouse skin tissue. Pathological changes of skin tissue caused by ultraviolet radiation and the arrangement of collagen were observed by Hematoxylin-Eosin (HE) staining and scanning electron microscopy (SEM). Interleukin 1β (IL-1β), IL-6, and IL-10 were detected using the quantitative real-time reverse transcription-polymerase chain reaction (qPCR) and Enzyme Linked Immunosorbent Assay (ELISA). The concentration and expression of these proinflammatory cytokines was associated with the presence of nuclear factor (NF)-κB. The results show that MAA compounds from Porphyra yezoensis could suppress UV-induced photoaging of skin by inhibiting the reduction of endogenous antioxidant enzymes. Compared to the control group, the concentrations of SOD, GSH-Px, and CAT increased significantly in skin tissue homogenate following the external administration of MAAs (p < 0.05, p < 0.01), while the content of MDA decreased significantly (p < 0.05). Meanwhile, the administration of MAAs was associated with down-regulations in the concentration and mRNA expression of NF-κB, IL-1β, IL-6, and IL-10. The results suggest that MAAs could protect skin from photodamage by increasing antioxidant enzyme activities and inhibiting inflammation.